2004
DOI: 10.1001/archpsyc.61.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cortical-Limbic Pathways in Major Depression

Abstract: Like other antidepressant treatments, CBT seems to affect clinical recovery by modulating the functioning of specific sites in limbic and cortical regions. Unique directional changes in frontal cortex, cingulate, and hippocampus with CBT relative to paroxetine may reflect modality-specific effects with implications for understanding mechanisms underlying different treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
225
1
11

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 970 publications
(253 citation statements)
references
References 93 publications
11
225
1
11
Order By: Relevance
“…44,45 Moreover, a significant increase in glucose metabolism in the dACC was seen in responders to CBT for major depression. 46 Taken together with these prior findings, our results suggest that dACC activation might be a common mechanism of action required for response to CBT across disorders.…”
Section: Discussionsupporting
confidence: 82%
“…44,45 Moreover, a significant increase in glucose metabolism in the dACC was seen in responders to CBT for major depression. 46 Taken together with these prior findings, our results suggest that dACC activation might be a common mechanism of action required for response to CBT across disorders.…”
Section: Discussionsupporting
confidence: 82%
“…Further, while hundreds of studies have shown that cognitive behavior therapy (CBT) can effectively change the thought processes and behaviors of adults with various types of psychopathology (Hofmann et al 2012), there is strong evidence to suggest that these cognitive and behavioral changes are associated with neurological changes when assessed with MRI and fMRI (Kandel 2006;Jokić-Begić 2010;Schwartz and Begley 2002;Goldapple et al 2004). Similarly, experiments have shown both mindfulness and compassion-focused meditation to be effective in reducing anxiety, depression, and anger while enhancing emotion regulation, empathy, and psychological well-being (e.g., Eberth and Sedlmeier 2012;Hofmann et al 2011).…”
Section: Anomalies That Challenged the Old View Of The Brainmentioning
confidence: 99%
“…39,114 Cognitive behavioral therapy (CBT) and interpersonal therapy (IPT), two forms of psychotherapy studied for efficacy in the treatment of depression, have effects on affective circuitry that are distinct from those of antidepressant medication. 37,115,116 A "top-down" mechanism has been postulated in which these therapies may enhance function of the orbital cortex/anterior insula and other cortical regions to more effectively attenuate dysregulated limbic activity. 12,116 These findings support the hypothesis that it is an imbalance within these circuits, rather than any specific directional disturbance in a sin- gle region, that provides a neural substrate for mood dysregulation.…”
Section: Presumptive Mood Disorder Circuitsmentioning
confidence: 99%
“…37,115,116 A "top-down" mechanism has been postulated in which these therapies may enhance function of the orbital cortex/anterior insula and other cortical regions to more effectively attenuate dysregulated limbic activity. 12,116 These findings support the hypothesis that it is an imbalance within these circuits, rather than any specific directional disturbance in a sin- gle region, that provides a neural substrate for mood dysregulation. Magnetic seizure therapy (MST), an experimental technique using a magnetic field to induce a seizure, is currently being investigated in the treatment of depression by Lisanby et al 117 They have reported some preliminary evidence that MST may have fewer cognitive side effects than ECT.…”
Section: Presumptive Mood Disorder Circuitsmentioning
confidence: 99%